Batch anaerobic digestion of deproteinated malt whisky pot ale using different source inocula. (January 2018) - Barrena, Raquel; Traub, Julio E.; Gil, Cristina Rodriguez; Goodwin, Julian A.S.; Harper, Alan J.; Willoughby, Nik A.; Sánchez, Antoni; Aspray, Thomas J.
Highlights: Deproteination is a potential pre-treatment for anaerobic digestion. A novel process reduced chemical oxygen demand and copper loading in pot ale. Methane yield was different for untreated pot ale using two inocula. No difference was observed for treated pot ale with the two inocula. Removed protein has potential resale value in the feed and food industries. Abstract: A novel process has been developed for the selective removal of protein from pot ale with recovered protein holding potential as a value-added by-product for the whisky industry. The purpose of this work was to assess the effect of deproteination on pot ale physicochemical characterisation and anaerobic digestion (AD) treatment. Pot ales were taken from five malt whisky distilleries and tested untreated, after centrifugation/filtration and after deproteination at laboratory or pilot scale. At laboratory scale, the deproteination process removed around 20% of total chemical oxygen demand (tCOD) from untreated pot ale and at least 30% dissolved copper from centrifuged pot ale. Biochemical methane potential of untreated, filtered and deproteinated pot ale obtained at pilot scale has been determined using two types of inocula from different source. Average methane yield values of 554 ± 67, 586 ± 24 and 501 ± 23 Nl CH4 kg −1 VS were obtained for untreated, filtered and deproteinated pot ale respectively. A significant difference in methane yield was only observed for untreated pot ale using the two types of inocula. Specifically, when using a non-adapted inoculum untreated pot ale biogas yield was significant lower suggesting inhibition of the AD process. As no significant differences were found for treated pot ale (filtered and deproteinated) with the two inocula it suggests, deproteination may have a positive effect on AD start-up. The results present a clear case for continuation of this work and evaluating the effect on continuous AD.